Coping Competence and Social Support on Job Performance in the Nigerian Tourism Industry - ARUBAYI, Olusoji Damaro; EJETA, Dafe Marcus (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
This study examined coping competence, social supports and job performance in the tourism industry in Nigeria. The survey research design was adopted via questionnaire and was administered to three hundred and five (305) employees of tourism companies. Data obtained were analyzed using descriptive and inferential statistical tools. Findings revealed that coping competence and social support significantly and positively affect job performance in the tourism industry. The implication is that employees in the tourism industry have high level of coping competence towards handling stressful situations in the workplace and they receive maximum social supports from superiors and colleagues resulting in enhanced job performance. The study recommends that since coping competence improve job performance, management of the tourism industry should periodically assess employees’ coping competence regularly to ensure that negative coping skills are eliminated from the work environment. More so, management of the tourism industry should incessantly support employees in their day-to-day tasks in order to improve job performance.